F4/80: the macrophage-specific adhesion-GPCR and its role in immunoregulation. - Lin, H; Stacey, M; Stein-Streilein, J; Gordon, S (2010)
As a macrophage-restricted reagent, the generation and application of the F4/80 mAb has greatly benefited the phenotypic characterization of mouse tissue macrophages for three decades. Following the molecular identification of the F4/80 antigen as an EGF-TM7 member of the adhesion-GPCR family, great interest was ignited to understand its cell type-specific expression pattern as well as its functional role in macrophage biology. Recent studies have shown that the F4/80 gene is regulated by a novel set of transcription factors that recognized a unique promoter sequence. Gene targeting experiments have produced two F4/80 knock out animal models and showed that F4/80 is not required for normal macrophage development. Nevertheless, the F4/80 receptor was found to be necessary for the induction of efferent CD8+ regulatory T cells responsible for peripheral immune tolerance. The identification of cellular ligands for F4/80 and delineation of its signaling pathway remain elusive but are critical to understand the in vivo role of this macrophage-specific adhesion-GPCR.